Von Meyenburg’s complexes: the need for timely diagnosis - Padmanabhan, Kameswari; Ramachandran, Rajoo; Ramachandran, Rajoo; Radhakrishnan, Prabhu Radhan; Radhakrishnan, Prabhu Radhan; Prithiviraj, Periasamy Varadaraju; Prithiviraj, Periasamy Varadaraju (International Surgery Journal, 2016)
Von Meyenburg’s complexes are rare benign findings in the liver. But recent evidence suggests the incidence of carcinoma in a few percent of cases. Here, we present a case with ultrasound and computed tomography imaging findings of Von Meyenburg Complexes and necessitate the importance of follow-up investigations. Case presentation of a 48 year old lady presenting with vague abdominal pain. Lab investigations were done and she was further imaged with ultrasound with GE Voluson 730 and contrast enhanced computed tomography with 64 slice GE VCT both of which are presented in the report. A diagnosis of Von Meyenburg’s complexes was given in accordance with USG and CT findings. The need for prompt diagnosis and follow-up is necessary since there has been recent evidence stating the association of biliary hamartomas and cholangiocarcinomas. In this setting, it is prudent the clinician be aware of this simple, yet rare entity.